RNA Recognition Motif 2 of Yeast Pab1p Is Required for Its Functional Interaction with Eukaryotic Translation Initiation Factor 4G - Kessler, Steven H. (American Society for Microbiology, 1998)
The eukaryotic mRNA 3′ poly(A) tail and its associated poly(A)-binding protein (Pab1p) are important regulators of gene expression. One role for this complex in the yeast Saccharomyces cerevisiae is in translation initiation through an interaction with a 115-amino-acid region of the translation initiation factor eIF4G. The eIF4G-interacting domain of Pab1p was mapped to its second RNA recognition motif (RRM2) in an in vitro binding assay. Moreover, RRM2 of Pab1p was required for poly(A) tail-dependent translation in yeast extracts. An analysis of a site-directed Pab1p mutation which bound to eIF4G but did not stimulate translation of uncapped, polyadenylated mRNA suggested additional Pab1p-dependent events during translation initiation. These results support the model that the association of RRM2 of yeast Pab1p with eIF4G is a prerequisite for the poly(A) tail to stimulate the translation of mRNA in vitro.